The effects on some sport organisations of coronavirus pandemic - Dalo, D. F. A.; Bingölbali, A.; Sarigül, V. (Anatolia Sport Research, 2021)
Aim: Sport is an important part of individual life. The sports sector, like the rest of the sectors and human activities, was negatively affected by the Corona pandemic. The purpose of this study is to examine the effectiveness of the COVID-19 pandemic to sports organizations around the world. Material and Method: The COVID-19 has affected international sports events on all continents. Results in the world's health, education, money and trade institutions and sports activities are similar. Some sporting events such as Tokyo 2020 Olympics Game, Euro 2020 have been canceled or postponed. Results: As a result of this study, it was seen that the effects of this epidemic on all sports industries in the world are still enormous. Conclusion: The conclusion of this study turns out that the deadly epidemic has negatively affected the public sectors and sports in particular such as "European Football Championship, Copa America Championship, Olimpic Games, Football leagues and other activities in all countries of the world. It was determined that there is a decline in sports in all countries of the world, especially in countries that practice true professionalism. It has also been found to have an impact on the race to contract over a million professionals.